Sustainable Development of Agricultural Production Based on the Use of the Resource Potential of the Region - KAZAMBAYEVA, A. M.; AIESHEVA, G. A.; YESENGALIYEVA, S. M. (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
Sustainable development of agricultural production objectively necessitates the efficient use of the resource potential of regions, a combination of which plays a decisive role in shaping the economic development rate and increasing production volumes, competitiveness of domestic agricultural products, labor productivity, and the ability to quickly adapt to a changing socioeconomic situation. The resource potential of the agricultural sector is of paramount importance in the formation of the specialization foraregionor district. Due to this, the present work substantiates the need to study the specialization of regions in agriculture, taking the efficient use of their resource potential into account, which will allow to submit forecasts for the development of regions of the Republic of Kazakhstan on the optimal use of agricultural land for the production of specific types of products. This study has been conducted for the western region of Kazakhstan, and a comprehensive assessment of the potential of the regions has been given in order to increase the cost-effective types of agricultural products and labor productivity.